CT enterography in the evaluation of Crohn's disease - dos Santos, Carlos Henrique Marques; da Silva Menezes, Jovino Nogueira; Nunes, Thiago Franchi; de Assis Martins, Letícia (Journal of Coloproctology, 2015)
Proposition Crohn's disease (CD) is a chronic inflammatory process that affects various parts of the gastrointestinal tract, from the mouth to the anus with unknown etiology and variable clinical presentation. CD diagnosis is based on clinical and complementary tests. Among the complementary tests, enterography with CT enterography has shown good results in the evaluation of this disease.Methods The patients evaluated were submitted to a questionnaire on the clinical manifestations of the disease and an CT enterography was obtained. The studies were reviewed by an experienced radiologist looking for radiological signs of CD.Results The mean age was 40 years, with a predominance of women. The main clinical manifestations are diarrhea in 24 (70%), hematochezia in 19 (55%), abdominal pain in 29 (85%) and weight loss in 22 (64%) patients. The main findings on CT enterography were an intestinal wall enhancement signal in 23 patients (67%), vascular engorgement (vasa recta) in 20 (58%), parenteral fat densification in 14 (41%), intestinal wall thickening in 22 (64%), and lymph node enlargement in 17 (50%) of patients.Conclusion This study showed that CT enterography presents a good assessment of intestinal involvement by CD.
Keywords: Crohn's disease; Enterography; Diagnosis